STRUCTURE-FUNCTIONAL PECULIARITIES OF MYOCARDIAL LEFT VENTRICULAR REMODELING IN PATIENTS WITH MYOCARDIAL INFARCTION ON SANATORY RECOVERY STAGE - Vlasenko, O.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
One hundred and seventeen patients with postinfarct cardiosclerosis were examined. Left ventricular remodeling was established in 80,3 % patients. It was found to have developed concentric hypertrophy of left ventricle (LV) and moderate LV diastolic dysfunction mainly with impaired relaxation in 55,5 % patients. About 24,8% patients had more significant LV structural and geometric derangement with a tendency for the development of eccentric hypertrophy of the LV, as well as more marked systolic and diastolic dysfunction.